Relevance of curriculum content for learning ICT-mediated teaching: perspectives from Tanzanian computer science student teachers and tutors - Chalale, George; Maro, Wadrine Onael; Tarmo, Albert (Papers in Education and Development, 2025)
This study explored the perspectives of computer science student-teachers and tutors on the relevance of curriculum content for learning ICT-mediated teaching in Tanzanian diploma teachers’ colleges. Using a qualitative multiple-embedded case study design, data were collected from 30 participants through focus group discussions, interviews, and document analysis. The findings indicate that both student-teachers and tutors consider the ICT curriculum relevant, particularly topics such as computer applications, networking, and programming languages, which support lesson planning, teaching, and assessment using ICT. The study concludes that effectively integrating these technological topics enhances ICT-mediated teaching skills among future educators. It recommends that teacher education institutions, including the Tanzania Institute of Education (TIE), embed these topics more comprehensively into syllabi for science and mathematics student-teachers, emphasising digital literacy and technical proficiency.